Dampak Pandemi COVID-19 Terhadap Pola Pekerjaan Petani - Norma Yuni Kartika; Sheilia Novitriani (Pancanaka, 2021)
Government policies which taken to prevent the spread of Covid-19 have an impact on the labor sector, including people who work in the agricultural sector. Purpose of this study is to determine changes in the work patterns of farmer household heads during the pandemic. The research location is in Andaman Village, Anjir Pasar District, Barito Kuala Regency, South Kalimantan Province, with the majority of the population work as farmers who are selected purposively. The sample in this study is families with the main occupation of the household heads are farmers and have wives aged 15-49 years. The sample size of 30 respondents is determined using the quota sample method and taken randomly. The analysis using a descriptive analytical manner with a simple statistical method. Findings of the study show that 13.33 percent of household heads lost their main jobs as farmers. The same pattern occurs in the side jobs, before the pandemic 36.7 percent of farmer household heads do not have side jobs and after the pandemic, the percentage increase to 80 percent. Indeed the household heads who loses their main job as farmers and lose the side job have an impact on the economy of the families.